(untitled) (International Journal of Language, Literacy and Translation, 2025)
Gender identity and expressions have shifted from invariable to variable at birth. This means that it can shift and change at any given time. The concept of gender queer has been broadly accepted in many Western countries, such as the United States, but it has not been widely introduced in China. As the media is a means of exchanging cultures and knowledge, an English film about queer gender is a critical aspect for Chinese people who are only beginning to gain access to related knowledge. Linguistic techniques, cultural elements, and ideological differences determine subtitle translation. These cultural and ideological connotations often reflect assumptions that may vary from one culture to another, revealing different ways of understanding and expression. A small bilingual parallel corpus with subtitles of 10 queer films is investigated here, aiming to see the cultural difference and to analyse translation strategies for translating the culture-loaded words and expressions. Words and expressions related to gender queer are selected for analysis, including “lesbian”, “dyke”, “butch”, “gay”, “faggot”, “poofter”, “camp”, “bisexuality”, “transgender”, and “transvestite”. It is critical for subtitlers to translate gender queer films from a queer perspective, follow Vinay and Darblenet’s translation model and try to soften, desexualize, and sanitize the culture-loaded words and expressions, and make sure translators do not add extra negative attitudes and ideology into the translation. Only by maintaining a “neutral attitude” throughout the translation process can these subtitles positively enhance audiences' understanding and acceptance of gender queer people.